Expression of Linguistic-Cultural Concepts in Ethnonames - Shodievna, Kurbanazarova Nargis (International Journal on Integrated Education, 2023)
In this article, the specific aspects of the expression of ethnonyms in linguistic and cultural concepts at the stages of historical development are highlighted, and the importance of ethnonyms in the level of application of linguistic and cultural concepts is discussed.